Ex dividend day stock price behavior: discreteness or tax-induced clienteles? - Bali, Rakesh; Hite, Gailen L. (Journal of Financial Economics, 1998)
Since prices are constrained to discrete tick multiples while dividends are essentially continuous, ex day price changes will not equal dividends. We argue that the expected price drop is strictly less than the dividend but within one tick of the dividend. The price-drop-to-dividend ratio will (i) be less than one, (ii) increase with dividends generally, and (iii) decline between tick multiples, giving a sawtooth pattern in the data. Since dividends and dividend yields are highly correlated, discreteness will give the impression of tax-induced dividend clienteles even if there are none. Taxable cash dividends and nontaxable stock dividends exhibit similar ex day behavior.